Bài 1:
S1 = 1 + 2 + 22 + 23 + ... + 263
2.S1 = 2 + 22 + 23 + 24 + ... + 264
2S1 - S1 = (2 + 22 + 23 + 24 + ... + 264) - (1+2+22+22 + 23 + ... + 263)
S1 = 2 + 22 + 23 +...+ 264 - 1 - 2 - 22 - 23 - ... - 263
S1 = (2 - 2) + (22 - 22) + (23 - 23) + ... + (263 - 263) + 264 - 1
S1 = 264 - 1
Bài 2: S= 1 + 3 + 32 + ... + 32000
3.S = 3 + 32 + 33 + .... + 32001
3S - S = ( 3 + 32 + 33 + ... + 32001) - ( 1 + 3 + 32 + ... + 32000)
2S = 3 + 32 + 33 + ... + 32001 - 1 - 3 - 32 - ... - 3200
2S = (3 - 3) + (32 - 32) + (33 - 33) + (32000 - 32000) + (32001 -1)
2S = 32001 - 1
S = \(\dfrac{3^{2001}-1}{2}\)
Bài 3:
A = 1 + 2 + 22+ ...+ 22007
2.A = 2 + 22 + 23 + ... + 22008
2A - A = (2 + 22 + 23 + ... + 22008) - (1 + 2 + 22 + ... + 22007)
A = 2 + 22 + 23 + ... + 22008 - 1 - 2 - 22 - ... - 22007
A = (2 - 2) + (22 - 22) + (23 - 23) + ... + (22007 - 22007) + (22008-1)
A = 22008 - 1
Bài 4: A = 1 + 3 + 32 + ... + 330
3.A = 3 + 32 + 33 + ... + 331
3A - A = (3 + 32 + 33 + ... + 331) - ( 1 + 3 + 32 + ... + 330)
2A = 3 + 32 + 33 + .... + 331 - 1 - 3 - 32 - ... - 330
2A = (3 - 3) + (32 - 32) + (330 - 330) + (331 - 1)
2A = 331 - 1
B = 331 : 2 ⇒ 2B = 331
2B - 2A = 331 - (331 - 1)
2.(B - A) = 331 - 331 + 1
2.(B - A) = 1
B - A = \(\dfrac{1}{2}\)
Bài 5:
A = 2 + 22 + 23 + .... + 260
A = 21 + 22 + 23 + ... + 260
Xét dãy số 1; 2; 3;...;60 dãy số trên có số số hạng là:
(60 - 1) : 1 + 1 = 60 (số hạng)
A có 60 hạng tử vì 60 : 2 = 30 nên nhóm hai số hạng liên tiếp của A thành nhóm ta được:
A = (2 + 22) + (23 + 24) + ... + (259 + 260)
A = 2.(1 + 2) + 23.(1 + 2) + ... + 259.(1 + 2)
A = 2.3 + 23.3 + .... + 259.3
A = 3.(2 + 23 + ... + 259)
Vì 3 ⋮ 3 nên A = 3.(2 + 23 + ... + 259) ⋮ 3 (đpcm)